Human germline editing is not prohibited by the Oviedo Convention: An argument. (June 2019) - Beriain, Iñigo de Miguel; Armaza, Emilio Armaza; Sánchez, Aliuska Duardo
Human germline gene editing has ignited wide-ranging debates on the ethical and legal issues involved. The text of the Oviedo Convention is particularly relevant here, as it remains the only international legally binding instrument on the protection of human rights in the biomedical field which considers human genome modification. However, it is often misinterpreted. Indeed, most of the academic literature assumes that Article 13 forbids germline gene editing. This article seeks to demonstrate that this belief is mistaken. To this purpose, it develops a general analysis of the Convention, its Explanatory Report, and its historical background. As a result, it argues that the Convention does not veto genetic editing for basic research purposes, but only its clinical application on human embryos to be transferred into a womb. Nevertheless, it recommends a revision of the clause according to the original intention of the Convention.